Pengaruh Latihan Side-To-Side Shuffle Jump terhadap Peningkatan Daya Ledak Otot Tungkai - Arfon Meirony; Lucy Oktavani (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2018)
The purpose of this study was to determine the effect of side-to-side jump training on increasing leg muscle explosive power. This research was an experimental research. The sampling technique used in the research was purposive sampling with 17 samples that were given an early test of vertical jump (modified sargent jump) and followed by the treatment of 14 sessions. The latest test was the post test to see the effect of the exercise. T-test was used to see the effect of the significant mean α 0,05. The results of the posttest mean was 98.26 and preetest mean was100.45. The hypothesis research was accepted because the result of ttest (6.22)>ttable (2.11). Conclusion, Side-to-Side Shuffle Jump exercises affect the increase of explosive limb muscle strength of Bung Hatta University Physical, Health and Recreation Education Keywords: Side-to-Side Shuffle Jump, Leg Muscles Explosive Power